Purposes and degrees of commodification: Economic instruments for biodiversity and ecosystem services need not rely on markets or monetary valuation (2015)
Commodification of nature refers to the expansion of market trade to previously non-marketed spheres. This is a contested issue both in the scientific literature and in policy deliberations. The aim of this paper is to analytically clarify and distinguish between different purposes and degrees of commodification and to focus attention to the safeguards: the detailed institutional design. We identify six degrees of commodification and find that all ecosystem services policies are associated with some degree of commodification but only the two highest degrees can properly be associated with neoliberalisation of nature. For example, most payments for ecosystem services (PES) are subsidy-like government compensations not based on monetary valuation of nature. Biodiversity offsets can be designed as market schemes or non-market regulations; the cost-effectiveness of markets cannot be assumed. To avoid the confusion around the concept ‘market-based instrument’ we suggest replacing it with ‘economic instruments’ since relying on the price signal is not the same thing as relying on the market. We provide a comprehensive framework emphasising the diversity in institutional design, valuation approaches and role of markets. This provides flexibility and options for policy integration of biodiversity and ecosystem services in different countries according to their political and cultural context.